x = e, 5, 7, 10, 12
y = 10, 13, 19, f, 34
a. f = 28; e = 4
b. e = 28; f = 4
c. f = 30; e = 2
d. e = 30; 5 = 2
4 answers
y=3x-2 .....
so what is the answer
Assume a straight line.
As x increases by 2 (5-7) y increases by 6 (13-19).
So try y = 3x
But, 13 - 3*5-2. So, try
y = 3x-2
it works for all the known pairs. So, fill in e and f.
As x increases by 2 (5-7) y increases by 6 (13-19).
So try y = 3x
But, 13 - 3*5-2. So, try
y = 3x-2
it works for all the known pairs. So, fill in e and f.
sorry. You have the equation.
Plug in the given x or y value and solve for e or f.
You gotta do something here, dontcha?
Stop looking for freebies...
Plug in the given x or y value and solve for e or f.
You gotta do something here, dontcha?
Stop looking for freebies...